1994
DOI: 10.1093/jmedent/31.4.600
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Depletion Affects Blood-Feeding but Not Host-Seeking Ability in Aedes triseriatus (Diptera: Culieidae)

Abstract: The host-seeking and blood-feeding abilities of Aedes triseriatus (Say) were evaluated after treatment with the amine depleting drugs alpha-methyl-tyrosine (AMT) and alpha-methyl-tryptophan (AMTP). High-performance liquid chromatography with electrochemical detection (HPLCED) was used to demonstrate that AMTP depleted serotonin levels, whereas AMT reduced dopamine levels. The host-seeking ability (evaluated with an olfactometer) of Ae. triseriatus was not altered by treatment with either AMT or AMTP. Blood-fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…This is consistent with the observed role of 5-HT in appetite modulation in numerous species, including mammals [Lucki, 1992] and insects [e.g. Dacks et al, 2003;Novak and Rowley, 1994;Novak et al, 1995]. While glutamate-and FMRFamidecontaining fibers are also present within the proventriculus, they are distinct from those that are serotonergic [Budnik et al, 1989].…”
Section: Introductionsupporting
confidence: 86%
“…This is consistent with the observed role of 5-HT in appetite modulation in numerous species, including mammals [Lucki, 1992] and insects [e.g. Dacks et al, 2003;Novak and Rowley, 1994;Novak et al, 1995]. While glutamate-and FMRFamidecontaining fibers are also present within the proventriculus, they are distinct from those that are serotonergic [Budnik et al, 1989].…”
Section: Introductionsupporting
confidence: 86%
“…Serotonin depresses feeding, whereas low neuronal serotonin levels increase appetite of Drosophila larvae (Neckameyer, 2010). In contrast, adults of the mosquito Aedes triseriatus respond to depletion of serotonin levels with a decrease in the amount of blood taken during feeding and in numbers of feeding episodes, but with no change in host-seeking behavior, suggesting that serotonin stimulates feeding (Novak and Rowley, 1994). The apparent difference in the roles of serotonin on appetite of larval and adult mosquitoes merits further study.…”
Section: Effects Of Paroxetine On Behaviormentioning
confidence: 98%
“…Serotonin also modulates insect feeding behavior. Serotonergic systems inhibit feeding in the locust, the ant, adults of two species of fly, an aphid, a cockroach and larval Drosophila (Dacks et al, 2003;Kaufmann et al, 2004;Falibene et al, 2012;Neckameyer, 2010), although serotonin appears to stimulate feeding by the adult mosquito Aedes triseriatus (Novak and Rowley, 1994). As in vertebrates, serotonergic pathways inhibit appetite and feeding behavior in insects (Gillette, 2006;Halford et al, 2007).…”
Section: Serotonin and Behaviormentioning
confidence: 99%
“…This process stimulates water absorption by the midgut and urine formation by the Malpighian tubules (Te Brugge et al, 2009). Indirect evidence suggests that serotonin release also occurs in mosquitoes during the hematophagic process (Novak and Rowley, 1994;Novak et al, 1995;Clark et al, 2009). Even among the non-hematophagous larvae of mosquitoes, studies have shown that serotonin acts on the midgut to increase the transepithelial voltage and, consequently, the rate of alkalization (Onken et al, 2008;Onken and Moffet, 2009).…”
Section: Introductionmentioning
confidence: 99%